Riesgo de cifoescoliosis en adolescentes de 12 a 17 años del Colegio Calasanz del cantón Loja. - Ochoa Herrera, Santiago Fernando (2016)
The present work was done to considering that the Kyphoscoliosis is a disease that affect whit increased risk to boys and teenagers for their development process. So in this work was proposed: determine the inside of Kyphoscoliosis, identify which is the most vulnerable gender and establish which is the range of age the most affected to teenagers between 12 and 17 years at Calasanz high School, for a descriptive and a cross sectional study, in which it analyzed 210 students by the test of Adams and the plumb line test. The collect dates was made on March of the present year, to determine an incidence of kyphoscoliosis 4%, the most vulnerable gender are women around the 6% and the range most affected age are teenagers between 12 to 13 years with 45%. That is why it is recommended realize checks and tests to identify in a time the Kyphoscoliosis risks that may be affecting teenagers and are possibly causing damage to your health. Key words: Risk of Kyphoscoliosis; Incidence rate; Kyphosis; Scoliosis; Teenagers